Theoretical Study of Sequential Centrifugal Partition Chromatography - Völkl, Johannes; Arlt, Wolfgang; Minceva, Mirjana (Aiche Journal, 2013)
Sequential centrifugal partition chromatography (sCPC) is a novel cyclic liquid-liquid chromatographic process. Each cycle comprises two steps, which differ by the liquid phase used as a mobile phase (upper or lower phase) and its flow direction. The feed is continuously separated into two product streams, which are collected alternately. The process includes six (four flow rates and two-step durations) interconnected operating parameters. In this work, by imposing a complete separation of a binary feed mixture and using the assumption of instantaneous solutes partition equilibrium, a set of constraints on the sCPC unit operating parameters is derived. Using these constraints, a region of complete separation, composed of a set of combinations of the two-step times, can be defined for a preselected feed and mobile phase flow rates. The approach is validated by simulation of a binary mixture separation in a sCPC using the cell model. (C) 2012 American Institute of Chemical Engineers AIChE J, 59: 241-249, 2013
Keywords: countercurrent chromatography; sequential centrifugal partition chromatography; true moving bed; operating parameters; modeling; simulation